2021
DOI: 10.1155/2021/6633178
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Knowledge and Practices in Medicine Dispensing between Retail Medicine Shops and Model Pharmacies in Dhaka Metropolis

Abstract: Model pharmacy has been adopted recently to upgrade the healthcare delivery system in Bangladesh. This study was aimed to analyze and compare the effectiveness of drug dispensing patterns, practices, and knowledge of both clients and dispensers of model pharmacies over traditional retail medicine shops. Two established methods, namely, client simulated method (CSM) and provider interview method (PIM), were employed to determine the practice differences in 90 retail medicine shops and 90 model pharmacies in and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Our study has further confirmed from observation that the trained Grade C pharmacists had better medicine dispensing practices, correct labeling of medicines and less frequent dispensing of medicines without prescription than the non-trained Grade C pharmacists, which are similar to the previous studies in Tanzania and Bangladesh indicating that training is a very important tool for improving knowledge of correct dispensing of medicines by Grade C pharmacists in Bangladesh ( Valimba et al, 2014 ; Chowdhury et al, 2018 ; Begum et al, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our study has further confirmed from observation that the trained Grade C pharmacists had better medicine dispensing practices, correct labeling of medicines and less frequent dispensing of medicines without prescription than the non-trained Grade C pharmacists, which are similar to the previous studies in Tanzania and Bangladesh indicating that training is a very important tool for improving knowledge of correct dispensing of medicines by Grade C pharmacists in Bangladesh ( Valimba et al, 2014 ; Chowdhury et al, 2018 ; Begum et al, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…Both Grade A and Grade B pharmacists are eligible for obtaining pharmacy license and opening medicine shops ( PCB, 2023a ). However, due to shortage of qualified Grade A and Grade B pharmacists, the government has introduced a new cadre of pharmacy professionals known as Grade C pharmacists who required to have a Secondary School Certificate (10 years of schooling) and a “Grade C pharmacist certificate” by completing a 3-month training course jointly conducted by the Pharmacy Council of Bangladesh (PCB) and Bangladesh Chemist and Druggist Samity (BCDS) (an organization of drug dispensers) in order to become eligible for applying to the Directorate General of Drug Administration (DGDA) for a pharmacy license ( Mazid and Rashid, 2011 ; Bates et al, 2016 ; DGDA, 2016 ; Begum et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation